Rapid, Automated, and Specific Immunoassay to Directly Measure Matrix Metalloproteinase-9–Tissue Inhibitor of Metalloproteinase-1 Interactions in Human Plasma Using AlphaLISA Technology: A New Alternative to Classical ELISA - Pulido-Olmo, Helena; Rodríguez-Sánchez, Elena; Navarro-García, José Alberto; Barderas, María G.; Álvarez-Llamas, Gloria; Segura, Julián; Fernández-Alfonso, Marisol; Ruilope, Luis M.; Ruiz-Hurtado, Gema (Frontiers in Immunology, 2017)
The protocol describes a novel, rapid and no-wash one-step immunoassay for highly sensitive and direct detection of the complexes between matrix metalloproteinases (MMPs) and their tissue inhibitor of metalloproteinases (TIMPs) based on AlphaLISA® technology. We describe two procedures: i) one approach is used to analyze MMP-9-TIMP-1 interactions using recombinant human MMP-9 with its corresponding recombinant human TIMP-1 inhibitor; ii) the second approach is used to analyze native or endogenous MMP-9-TIMP-1 protein interactions in samples of human plasma. Evaluating native MMP-9-TIMP-1 complexes using this approach avoids the use of indirect calculations of the MMP-9/TIMP-1 ratio for which independent MMP-9 and TIMP-1 quantifications by two conventional ELISAs are needed. The MMP-9-TIMP-1 AlphaLISA® assay is quick, highly simplified and cost-effective, and can be completed in less than 3 hours. Moreover, the assay has great potential for use in basic and preclinical research as it allows direct determination of native MMP-9–TIMP-1 complexes in circulating blood as biofluid.